(untitled) (Economic studies journal, 2023)
The study aimed to highlight the reality of green banking in Libyan banks, and to find out the extent of the interest of Libyan institutions in banks, led by the Central Bank, through exposure to the reality of green banking in Libyan commercial banks, as well as the obstacles that prevent banks from financing projects to preserve the environment, which is known as green banking. The study was based on four variables, which are the banks’ attitude towards green finance, the degree of banking awareness of green banking, the impact of the transformation to Islamic banking, the central bank’s orientations and the banking management’s orientations. Data of this study was collected through a questionnaire, which are distributed on the study sample that consisted of (33) individual employees of Jumhouria Bank. The questionnaire was analyzed and treated with statistical measures using the statistical analysis method using the (SPSS) program. The results of the study concluded that all the variables are considered as the obstacles to green banking. The study recommended that the need for the Central Bank to employ and direct Libyan commercial banks towards green banking to create a safe work environment for the banking sector..